The Problem of Religious Freedom In the Practice of Amar Ma'ruf Nahi Munkar - Latief, Mohamad; Rizqon, Ahmad; Kusuma, Amir Reza; Kubro, Syaikhul (Universitas Islam Negeri Raden Intan Lampung, 2022)
The issue of religious freedom continues to grow. A number of figures and institutions are constantly campaigning for religious freedom to every level of society. This effort emerged after the right of religious freedom seems to have been misinterpreted by attitudes that were considered intolerant and did not respect differences. This writing is quite interesting to study, due to the strong assumption that everyone has the freedom to embrace religion and worship according to his religion, and everyone is free to believe in beliefs, express thoughts and attitudes, according to his conscience. This study is a literature review, the method used is descriptive method, and conclusions are drawn by using deductive thinking. The result of this study is that religion gives freedom to anyone to choose between religion or even being an atheist. The practice of amar ma'ruf nahi munkar is a religious order and does not violate religious freedom. Islam does not force someone to embrace a certain religion, but Islam obliges every Muslim to convey goodness, invites to the truth, and avoids disgraceful actions, such as Habib Abdullah's theory which says that the great symbol of religion is amar ma'ruf nahi munkar.